FRI0157 Altered expression of the spliceosome components in leukocytes subsets from patients with ankylosing spondylitis: association to disease pathogenesis and therapeutic response. (12th June 2018) - Ladehesa, L.; Castro, M.C.; Lopez-Pedrera, C.; Ortega, R.; Pedraza, S.; del Río, M.; Abalos-Aguilera, M.C.; Ruiz-Limon, P.; Perez-Sanchez, C.; Ibañez-Costa, A.; Parra-Manso, Y.; Barbarroja, N.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease for which the etiopathogenesis has not yet been fully clarified. Splicing is a post-transcriptional process involved in the RNA maturation. Recent studies have revealed that a pathological deregulation of the spliceosome is associated to several human diseases. Yet, the spliceosome alterations and their modulation in therapeutic response have not been described in AS Objectives: 1) To evaluate the potential deregulation of the spliceosome in AS leukocytes and their involvement in the disease pathophysiology. 2) To analyse the in vivo effects of anti-TNF drugs on the spliceosome components of AS leukocytes Methods: Thirty two AS patients and 29 healthy donors (HDs) were included in a cross-sectional study. Eight AS patients were selected for a three-month longitudinal study of response to anti-TNFα therapy. Disease activity was determined by BASDAI index and, CRP and ESR levels. Physical function was measured by the BASFI index, spinal mobility by the BASMI index, and structural damage by the mSASSS. The expression of selected components of the major-(n=12) and minor-spliceosome (n=4), and splicing factors (n=28) was evaluated in purified leukocyte by Fluidigm methodology; in parallel, inflammatory marker expression was determined by RT-PCR Results: Compared to HDs, a significant deregulation in the expression of splicing factors and spliceosome components was found in lymphocytes, monocytes and neutrophils from AS patients, being neutrophils which displayed the highest number of altered molecules. Interestingly, a specific altered profile of spliceosome members was observed when compared lymphocytes (U1, U4, U5, SRSF6), monocytes (CELF4, ESRP2, RBM3, SRSF3, TIA1) and neutrophils (FBP11, SF3BTV1, U6, U12, PTB, RBM17, MAGOH, SRSF5, SRSF10). Correlation studies revealed that inflammatory profile, disease activity (CRP, ESR, BASDAI) and structural damage (BASMI, mSASSS) were associated to the alteration of a vast number of spliceosome components in all the leukocyte subsets evaluated. In addition, the BASFI index correlated with the expression of SKIP and U6atac in neutrophils. Anti-TNFα treatment of selected AS patients reversed the altered expression of several spliceosome components and splicing factors in PBMCs (UA2F2, nSR100) and neutrophils (ESRP1, NOVA1, SND1, SRM160, SRSF1, CUGBP). Association studies demonstrated that disease remission was associated with reversing the altered expression of a high number of the spliceosome molecules References: [1] AS patients display a deregulation of the spliceosome components associated to disease function, activity, inflammation and structural damage. [2] Anti-TNFα therapy may reverse, at least partially, the altered expression of several spliceosome components and splicing factors. Alteration of the spliceosome may provide new biomarkers for disease and therapeutic response in AS. Funded:JA PI-0139–2017, ISCIII (RIER RD16/0012/0015) Disclosure of Interest: None declared